2015
DOI: 10.1111/adj.12310
|View full text |Cite
|
Sign up to set email alerts
|

Sugary drink consumption and dental caries in New South Wales teenagers

Abstract: Background: The consumption of water, milk and various sugary drinks and their relationship with the caries experience of a random sample of teenagers aged 14 to 15 years living in New South Wales, Australia was investigated. Methods: Data were obtained from both clinical and questionnaire components of the NSW Teen Dental Survey, 2010. The analyses allowed for various demographic and behavioural risk factors using caries experience (DMFT >0) and mean DMFT as the key outcome variables. Results: Males were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 19 publications
4
31
0
Order By: Relevance
“…In addition, 60% and 49% of younger and older children, respectively, who have soft drinks available at home, were also high junk food consumers. Such findings are of concern as frequent soft drink consumption replaces healthier beverages in the diet (such as water and milk) and may increase the risk of obesity, type 2 diabetes, dental caries, and bone fractures [40, 41]. Taken together, these associations may reflect the contribution of obesogenic household culture to unhealthy food consumption of children within these households [42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 60% and 49% of younger and older children, respectively, who have soft drinks available at home, were also high junk food consumers. Such findings are of concern as frequent soft drink consumption replaces healthier beverages in the diet (such as water and milk) and may increase the risk of obesity, type 2 diabetes, dental caries, and bone fractures [40, 41]. Taken together, these associations may reflect the contribution of obesogenic household culture to unhealthy food consumption of children within these households [42].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies focussing on physical attributes highlight differing experiences of oral health between genders and the widening gap in the burden of oral health for Indigenous children . Similarly, a large body of research has reported the effects of tooth brushing and diet on caries in Australian children . As substrate and bacteria/plaque are fundamental biological factors in dental caries, this explains why diet and oral hygiene are often included in research.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of sugary beverages such as CocaCola can be a cause of caries 38) , and caries is a one of the most frequent reasons for loosing dental hard tissue 39) . It should take into account that postponing toothbrushing can prevent hard tissue loss in nm or μm scale however the loss caused by caries can be more.…”
Section: Discussionmentioning
confidence: 99%